Storytelling on the Russia-Ukraine war: #CreativesForUkraine, a transmedia activism project in the European creatives industries - Palomo-Domínguez, Isabel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The research describes the storytelling created by the European creative community in response to the invasion of Ukraine. Methodologically, it includes a content analysis of the #CreativesForUkraine project creations and two questionnaires addressed to authors and recipients. The results show high harmony of sense and interpretation between the two poles of the communicative process. Among the conclusions, the storytelling that sympathizes with Ukraine prevails, reserving the role of dystopian villain to Vladimir Putin. Digital communication and transmediality are the critical factors for spreading the message and calling to action.